2018
DOI: 10.3389/fpsyt.2018.00590
|View full text |Cite
|
Sign up to set email alerts
|

Phobia of the Supernatural: A Distinct but Poorly Recognized Specific Phobia With an Adverse Impact on Daily Living

Abstract: The psychological and psychiatric literature has seldom appreciated the clinical fact that fears of ghosts and kindred supernatural worries may be a cause of intense discomfort, poor sleep, and socio-occupational impairment. In the present article, this claim is illustrated by the clinical features of six patients who developed intense anxiety when they had to sleep alone at night. The fears were first noticed in childhood and persisted into adolescence and adulthood. At these times, they were overwhelmed by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…VRET sessions are commonly conducted in the clinical settings of a therapist's office (Boeldt et al, 2019), which requires therapists to dedicate clinic space to VR arrangements and maintains travel burdens upon patients. It is common for people with phobias to avoid treatment and hide their symptoms, even from their own health care providers (Davidson, 2005;de Oliveira-Souza, 2018;Curcio and Corboy, 2020). Patients seeking phobia treatment often worry about embarrassing themselves in front of therapists (Bush, 2008).…”
Section: Benefits Of Vret + Tmhmentioning
confidence: 99%
“…VRET sessions are commonly conducted in the clinical settings of a therapist's office (Boeldt et al, 2019), which requires therapists to dedicate clinic space to VR arrangements and maintains travel burdens upon patients. It is common for people with phobias to avoid treatment and hide their symptoms, even from their own health care providers (Davidson, 2005;de Oliveira-Souza, 2018;Curcio and Corboy, 2020). Patients seeking phobia treatment often worry about embarrassing themselves in front of therapists (Bush, 2008).…”
Section: Benefits Of Vret + Tmhmentioning
confidence: 99%
“…The differential diagnosis of phobia of the supernatural includes sleep terror, epilepsy, other phobias, dissociative states of sleep, dementia and nocturnal panic attacks. 39 Spiritual presence events are the various anomalous, often vividly sensory, events which people attribute to spirits, gods, or other supernatural forces (Nagnaam, Lohita Lochanaam, Danda Dharaam, Deergha Kesha, Nakha, Stana etc. characters).…”
Section: Demonic Dreaming or Dreams With Supernatural Agentsmentioning
confidence: 99%
“…35 It has been found that the large majority of children pass a stage of fearing ghosts, but these fears tend to decline after adolescence. 39 The thematic content of childhood nightmares more often included being chased, evil presence, and falling. 33 Young children who develop chronic bad dreams have shown general distress and emotional psychopathology.…”
Section: Dreams Of Childrenmentioning
confidence: 99%
“…These beliefs likewise have implications for social identity theories of social rank, self esteem, and the belief systems that individuals hold for explanatory meaning in their lives (Tajfel and Turner, 1979;Dagnall et al, 2015b;Hill et al, 2019). Reports of ghosts and haunts may also reinforce or contextualize the anxieties of individuals who are already fearful of the paranormal (Lange and Houran, 1999;de Oliveira-Souza, 2018).…”
Section: Possibly Morementioning
confidence: 99%